A study of the relationship between media technology and the reading interests of freshmen high school students in Holy Family School of Quezon City - Cabanilla, Gianina Angela Celine O.; Yang, Jackson V. (Quezon City : Institute of Library and Information Science, University of the Philippines Diliman, 2003)
It is hypothesized that older adolescent girls have more interests than they have time to pursue them. In the former decades they were influenced mainly by what they read, in books or in newspapers. Then moving pictures became all powerful. About four decades ago, the radio became a source of ideas and experiences. In the last two decades, TV gained prominence. Adolescents are thus subject to immense pressures from media over which the schools have no control at all. The mass media are well established and are much too powerful to be ignored. Motives for reading are changing.
This study is an investigation of the relationship between media technology and the reading interests of freshmen high school students of Holy Family School of Quezon City enrolled in school year 2002-2003.All the one hundred fifty or 150 (100) questionnaires retrieved were utilized in the study. Majority of the respondents were influenced by media technology (television, radio and movies) regarding their reading interests (97.33).The findings further showed the students have positive reading interests and that they read various types of reading materials such as magazines (28), newspapers (8.67), comics (44.67) and books (18.67) but preferred fiction to non-fiction. Their most preferred media technology was television (T.V.) with 73.33 followed by movies with 17.33 and the least preferred was radio with 9.33.The student's preference for their favorite type of media technology was found to be consistent with the media technology's influences on their reading interests. Their main reasons for reading are to fill in free time (33.33), to gain information (28) and to improve their vocabulary (18.67). With regards to the relationship of media technology (television, radio and movies) and reading interests, the chi-square test was used to determine the significance of the variables. It was found out that all media technologies (television, radio and movies) had a significant relationship with reading interests. Recognizing the freshman students' reading interests, the librarians should acquire more updated books, magazines, etc. that will suit the reading interests of library users and also, Holy Family School should augment its audiovisual resources especially the Father Butiña Media Center to complement the reading interests of the students. Further, the researcher concludes that technology does not appear to be replacing reading but interacting with it and suggests that technology can be used to improve the quality of reading.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Holy Family School of Quezon City; High school students -- Books and reading -- Philippines -- Quezon City